2006
DOI: 10.1152/ajpendo.00500.2005
|View full text |Cite
|
Sign up to set email alerts
|

The gastroenteroinsular response to glucose ingestion during postexercise recovery

Abstract: -This study examined gastrointestinal hormone and peptide responses when glucose was ingested after prolonged exercise. Six endurance-trained male athletes ran on a treadmill for 2 h at 60% V O2 max. Immediately after the run, the athletes consumed 75 g of glucose in 250 ml of water (ExGLU) or flavored water as a placebo control (ExPL). On a separate visit, the athletes rested for 2 h and then consumed glucose (Con-GLU). During the first 60 min of recovery from exercise alone (ExPL), plasma vasoactive intestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 41 publications
4
45
0
Order By: Relevance
“…Similar to the present study, a transient increase in the plasma levels of GLP-1 in response to acute exercise was previously shown in athletes (O'Connor et al 1995(O'Connor et al , 2006 and in healthy unrestrained, normal weight volunteers (Martins et al 2007). The present finding first demonstrated that, while PYY 3-36 levels were more strongly increased in high intensity sessions than in those of moderate intensity, no significant difference was observed in GLP-1 levels between these two sessions.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to the present study, a transient increase in the plasma levels of GLP-1 in response to acute exercise was previously shown in athletes (O'Connor et al 1995(O'Connor et al , 2006 and in healthy unrestrained, normal weight volunteers (Martins et al 2007). The present finding first demonstrated that, while PYY 3-36 levels were more strongly increased in high intensity sessions than in those of moderate intensity, no significant difference was observed in GLP-1 levels between these two sessions.…”
Section: Discussionsupporting
confidence: 91%
“…Although not measured in the current study, changes in these hormones are unlikely to explain the more sustained increase in P-CTX in FED, as their responses to feeding favour decreased bone resorption [11,12]. In addition, the available evidence relating to the responses of these hormones to exercise, suggests either no change [45] or a similar direction of change to that with feeding [46,47]. Changes in Cortisol, PTH, leptin and ghrelin were also not significantly different between the two conditions.…”
Section: Nutrient Ingestion Changes the Circulating Concentrations Ofmentioning
confidence: 65%
“…This is the first study to address the effects of exercise on PYY levels in humans. A single study has previously demonstrated that running had no impact on postprandial GLP-1 levels when compared with a similar period of rest (O'Connor et al 2006). However, this study involved highintensity exercise and was performed in athletes.…”
Section: Discussionmentioning
confidence: 98%
“…As exercise is a major determinant in the EB equation, it is, therefore, of extreme importance to determine how these appetite-related hormones respond to exercise. However, research in this area is rather limited (Sullivan et al 1984, Greenberg et al 1986, Bailey et al 2001, O'Connor et al 2006. The purpose of this study was, therefore, to investigate the effects of an acute period of moderate intensity exercise, when performed in the fed-state, on postprandial levels of ghrelin, PYY, GLP-1 and PP in normal-weight subjects and to correlate potential alterations with changes in subjective feelings of appetite/ satiety and prospective food intake at a subsequent meal.…”
Section: Introductionmentioning
confidence: 99%